2020
DOI: 10.1002/aenm.202000467
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Polymerized High Internal Phase Emulsion Separators for High Performance Soft Batteries

Abstract: large areas available on the skin or within the body. [3] Intrinsically stretchable batteries effectively make use of available space while perfectly complying to deformations and maintaining comfort for the wearer. [4][5][6] Recent developments exploit high-energydensity materials, such as Zn and Li-ion based batteries, [7][8][9][10] to enhance battery capacity and close the gap to rigid-island designs. [11] Despite the progress in capacity and rechargeability, the principle design of planar intrinsically str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Surprisingly, the WF‐ X s were stretchable. Cyclic tensile stress–strain curves in Figure 5(A) showed that the WF‐ X s exhibited high tensile strains, with WF‐17 to be the largest at 155% and WF‐14 to be the least at 125%, which are much higher than the ultimate failure strain of 36% for elastic polyHIPEs from trimethylolpropane tris (3‐mercaptopropionate) and divinylbenzene 27 and of 40% for stretchable polyHIPEs from urethane diacrylate and 2‐ethylhexylacrylate 28 . WF‐17 showed the largest stress at 306 kPa while WF‐18 had the lowest stress at around 200 kPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the WF‐ X s were stretchable. Cyclic tensile stress–strain curves in Figure 5(A) showed that the WF‐ X s exhibited high tensile strains, with WF‐17 to be the largest at 155% and WF‐14 to be the least at 125%, which are much higher than the ultimate failure strain of 36% for elastic polyHIPEs from trimethylolpropane tris (3‐mercaptopropionate) and divinylbenzene 27 and of 40% for stretchable polyHIPEs from urethane diacrylate and 2‐ethylhexylacrylate 28 . WF‐17 showed the largest stress at 306 kPa while WF‐18 had the lowest stress at around 200 kPa.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic tensile stress-strain curves in Figure 5(A) showed that the WF-Xs exhibited high tensile strains, with WF-17 to be the largest at 155% and WF-14 to be the least at 125%, which are much higher than the ultimate failure strain of 36% for elastic polyHIPEs from trimethylolpropane tris (3-mercaptopropionate) and divinylbenzene 27 and of 40% for stretchable polyHIPEs from urethane diacrylate and 2-ethylhexylacrylate. 28 WF-17 showed the largest stress at 306 kPa while WF-18 had the lowest stress at around 200 kPa. An obvious hysteresis was observed to all the WF-Xs for the first cycle, while compared to the second loading cycle, the loading-unloading curves of the further cycles were mostly overlapped, showing their relatively high stability in tensile after the first cycle.…”
Section: Stretchabilitymentioning
confidence: 87%
“…Ultrathin gold nanowires have proved to be a good candidate for wearable sensors, [4,35] stretchable/transparent electrodes, [37] and supercapacitors. [38] Here, we further extended their applications as stretchable fuel cells for the electro-oxidation of ethanol upon mechanical deformation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34–36 ] It has not been used for deigning soft wearable energy devices until very recent report as a new type of ionically conductive separators in stretchable batteries. [ 37 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation